Psychology of Retention Theory, Research and Practice (Springer International Publishing, 2018)
This book offers a contemporary review of talent retention from the viewpoint of human resource management and industrial/organisational psychology. With a practical and relevant perspective it enriches critical knowledge and insight in the psychology of talent retention. It offers interpretation of difficult factors facing organisations such as the conceptualisation of talent, the forecasting of talent demand and supply, external and internal factors that influence talent attraction, development and retention, the alignment between talent management and business strategy. Also covered is the implementation of human resource practices and strategies in response to the needs of different organisational contexts and workforce characteristics. The chapter contributions will not only enrich knowledge and insight in the complex phenomenon of talent retention, but also advance new original ways of thinking and researching this critically important area of inquiry. The book is intended for graduate students and researchers as an overview of the topic of talent retention, practitioners will also find it informative.